Presence of immune complex-like material in sera of patients with paraproteinaemia. Issue 9 (September 1981) - Klein, F; Lafeber, G J; Jongepier-Geerdes, Y E; Cats, A; Kauffmann, R H; Michiels, J J
Abstract : Immunoglobulins of all classes as well as C3 are phagocytosed by normal human granulocytes from sera containing paraproteins. The material that was phagocytosed had the sedimentation properties of immune complexes. Cytostatic treatment did not seem to have a clearcut influence on the presence or absence of these complexes. There was little correlation with two other immune complex detecting tests. The Clq binding test was frequently found positive in paraproteinaemic sera but without apparent correlation to IgG phagocytosis. On the other hand the conglutinin binding test was rarely positive, although C3 was frequently phagocytosed.